Max Aub, Francisco Ayala : epistolario 1952-1972 / [introducción y notas] Ignacio Soldevila Durante - Soldevila Durante, IgnacioAyala, Francisco (1906-2009); Aub, Max (1903-1972)
Contiene :4 cartas facsimiles de Francisco Ayala y Max Aub | Índices